Continuous assessment in Oshikwanyama: a case study - Nghiueuelekuah, Soini Tuhafeni (Rhodes University, Faculty of Education, Department of Education, 2009)
This study is about Continuous Assessment (CA) in teaching and learning, a new concept and approach in independent Namibia. The country's education system was reformed shortly after independence in 1990 to fulfill the intention for Education for All. The Namibian education system then moved from a behaviorist to constructivist philosophy of education. The move made from one philosophy to another resulted in many changes in teaching and learning including changes in assessment in education. CA is born out of a constructivist philosophy. It is believed to facilitate learning with understanding. In this study I explored the understanding of Oshikwanyama teachers and their practice of CA in teaching and learning. Interviews, classroom observations and document analysis were used. The research focused on 10 participants in the Ohangwena and Oshana regions. The participants ranged from a Head of Department to members of the curriculum panel, subject advisors and Oshikwanyama subject facilitators as well as teachers at the classroom level. It was revealed that generally speaking, CA as a term is understood, but the practice is not well implemented. In the practice of CA, instead of learners being assessed for further learning, the emphasis is on scored marks without further assistance in learning. Further, the collection of marks during CA is often seen as largely for the purpose of contributing to the marks for summative final marks. Informal assessment which is part of CA was not given attention, which is a key factor preventing the effective use of CA in teaching and learning. Methods such as marking grids that are provided in the syllabus, as well as portfolios and learners' profiles, were not mentioned in the interviews nor observed as being in use. Participants in the study did acknowledge that they did not fully understand how best to implement CA. Overall, the evidence pointed to a conclusion that the identified shortcomings in the implementation of formative assessment is limiting the realization of the rich potential for CA as a day-to-day tool to facilitate learning for understanding in the observed classes.
Keywords: Educational tests and measurements -- Namibia -- Case studies; Kuanyama language -- Namibia -- Case studies; Kuanyama language -- Study and teaching -- Namibia -- Case studies; Language and education -- Namibia -- Case studies